2017
DOI: 10.1007/978-1-4939-6813-8_16
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroid Action in Plant Abiotic Stress Tolerance

Abstract: Brassinosteroids (BRs) are a class of plant steroidal hormones that play essential roles in plant growth and development. Systematic studies had first been undertaken concomitantly to determine both the effects of exogenous BR on stress phenotypes of Arabidopsis thaliana and Brassica napus (rapeseed) seedlings and the expression of stress marker genes in BR-treated and untreated seedlings. When reproducible and convincing evidence of the role of BR in stress tolerance had been obtained, molecular mechanisms un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 23 publications
1
17
0
1
Order By: Relevance
“…The pivotal role of ethylene on plant growth and abiotic stress response was discussed by Dubois and colleagues [80], who showed that an increasing number of transcriptome studies in plants exposed to abiotic stress suggested a role for ethylene under a broad range of stresses. Plant steroidal hormones like brassinosteroids were also involved in the plant abiotic stress response, including molecular mechanisms that confer tolerance against heat, cold, drought, and salt stress [81]. We also observed the (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…The pivotal role of ethylene on plant growth and abiotic stress response was discussed by Dubois and colleagues [80], who showed that an increasing number of transcriptome studies in plants exposed to abiotic stress suggested a role for ethylene under a broad range of stresses. Plant steroidal hormones like brassinosteroids were also involved in the plant abiotic stress response, including molecular mechanisms that confer tolerance against heat, cold, drought, and salt stress [81]. We also observed the (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…Brassinosteroids are a unique class of plant hormones that are essential for normal plant growth [120,121]. However, to date, the roles of these substances in plant leaf senescence have not been studied in depth.…”
Section: A Role Of Brassinosteroids and Ga In Leaf Senescence Of Red mentioning
confidence: 99%
“…Phytohormones play signi cant roles in regulating developmental processes and signal transduction networks that respond to various abiotic and biotic stresses. Brassinosteroid (BR), jasmonate (JA), gibberellin (GA), salicylic acid (SA), and auxin regulate plant growth, development, stress, and defense responses [4][5][6][7][8][9], but how phytohormones mediate the growth and stress trade-off is unclear.…”
Section: Introductionmentioning
confidence: 99%